The morphological lesson of the Algerian scholar Noureddine Abdelkader in his blog is the morphological message from complexity to facilitation - Abdulrahman, Fatima (Journal of Humanities & Social Sciences, 2019)
As language is the container of the idea of ​​the nation, and culture, and a means of understanding between the children and a tool to express among themselves, and part of its identity, and its personality was necessary for its children to maintain sound sound, and by controlling the rules, and delivery to the emerging generations in the simplest and easiest ways, Do not alienate them, this is what we find in the Algerian scientists in their blogs in general and the language of the language, especially those who tried to facilitate the linguistic sciences in general, and morphological especially because it is a difficult science in which the student needs to understand the nails to catch the rules so as not to slip in a simple way easy to preserve the T on the one hand, and on the other hand Granulation material has so entrenched in his mind, and this is what we find when Nur al-Din Abdul Qadir in his Morphological What is the Algerian sign, Noureddine Abdel-Kader ?, and what is his method of teaching exchange through the author of the letter Alsrafif ?, Is this really facilitated the rules of morphology and what is the purpose of that? And what is his way of teaching this morphological material?
Keywords: grammar; linguistic; morphology; lesson